Potensi Ekstrak Akuades Biji Pepaya sebagai Penghambat Pertumbuhan Khamir Penyebab Busuk Buah Tomat dan Stroberi (Life Science, 2022)
Papaya seeds are known to contain secondary metabolite compounds. These chemical compounds can be used by passing the extraction method with aquadest solvent where aquadest is an easily obtained material that facilitates its application in the community. This research aims to extend the shelf life of the fruit with in vitro testing and its application to the fruit directly (in vivo). The research designs used were complete randomized designs for in vitro and group randomized designs for in vivo tests. The medium used is YPMEA which is a specific medium for yeast growth. Papaya seeds used in the form of California papaya seeds that have been cooked are then extracted with aquadest solvent. The parameters used for in vitro testing are in the form of extract-inhibiting zone diameter around the paper disc while the parameters for in vivo tests are in the form of fruit storage, texture, aroma, and microbial sustainability in addition to isolates. The data were analyzed with a one-way Anava for in vitro testing and descriptive analysis for in vivo testing. Anava results showed that papaya seed aquadest extract has a significant effect on inhibition of germicidal ripening that causes rotten tomatoes and strawberries. The increase in the shelf life of the fruit in tomatoes increases by 2 days and strawberries by 3 days. Based on the results of the study, the use of papaya seed aquades extract concentration is 100% effective to increase the shelf life of the fruit. Biji pepaya diketahui mengandung senyawa metabolit sekunder. Senyawa kimia tersebut dapat digunakan dengan melewati metode ekstraksi dengan pelarut akuades dimana akuades merupakan bahan yang mudah didapatkan sehingga memudahkan penerapannya di masyarakat. Penelitian ini bertujuan untuk memperpanjang daya simpan buah dengan uji secara in vitro dan penerapannya pada buah secara langsung (in vivo). Rancangan penelitian yang digunakan yaitu Rancangan Acak Lengkap untuk in vitro dan Rancangan Acak Kelompok untuk uji in vivo. Medium yang digunakan yaitu medium YPMEA yang merupakan medium spesifik untuk pertumbuhan khamir. Biji papaya yang digunakan berupa biji papaya California yang telah masak kemudian diekstrak dengan pelarut akuades. Parameter yang digunakan untuk uji in vitro berupa diameter zona hambat ekstrak disekitar paper disc, sedangkan parameter untuk uji in vivo berupa daya simpan buah, tekstur, aroma, dan keberadaan mikroba selain isolat. Data dianalisis dengan Anava satu arah untuk uji in vitro dan analisis deskriptif untuk uji in vivo. Hasil Anava menunjukkan, ekstrak akuades biji papaya berpengaruh signifikan terhadap penghambatan pertumbuhan khamir penyebab busuk buah tomat dan stroberi. Pertambahan daya simpan buah pada buah tomat bertambah 2 hari dan buah stroberi 3 hari. Berdasarkan hasil penelitian, penggunaan ekstrak akuades biji papaya konsentrasi 100% efektif untuk menambah daya simpan buah Keywords: Aquadest extract; papaya seed; yeast ekstrak akuades; biji papaya; khamir